Columnar Cell Lesion and Apocrine Hyperplasia of the Breast: Is There a Common Origin? The Role of Prolactin-induced Protein. Issue 7 (August 2019) - Sciarra, Amedeo; Lopez, Gianluca; Corti, Chiara; Runza, Letterio; Ercoli, Giulia; Bonometti, Arturo; Despini, Luca; Blundo, Concetta; Gambini, Donatella; Fusco, Nicola
Abstract : Noninvasive breast lesions encompass a heterogeneous group of risk indicators and nonobligate precursors of breast cancer, such as apocrine hyperplasia (AH) and columnar cell lesions (CCLs). Given the different expression of ER and ER-regulated genes in AH and CCL, these two alterations are currently considered discrete conditions. However, whether they share early biologic changes is not clear to date. Here, we sought to define the clinicopathologic and immunohistochemical features of a prospective series of combined lesions made up by CCLs and AH forming a continuum within single terminal duct-lobular units. The study group included 19 cases, whereas 25 cases of synchronous contiguous CCLs and AH served as control group. The different components of each case were subjected to immunohistochemical analysis for ER, PR, AR, HER2, BCL2, CCND1, MUC1, and PIP. Although CCLs and AHs arising in continuity showed opposite patterns of ER expression, the PIP-positive apocrine signature was consistently present in both components. In conclusion, apocrine changes are highly recurrent in CCLs growing within foci of AH, regardless of the ER activation. Our results suggest that PIP-positive and PIP-negative CCLs are likely to represent biologically distinct conditions and that apocrine changes might occur earlier than ER activation in the natural history of breast precursor lesions.